Surgery in Montevideo at the Turn of the Century. Appendicectomies and Biliary Surgery - Praderi, Raúl (Cirugía del Uruguay, 1980)
The first appendectomies, cholecystostomies and gastro - enterostomies were performed in Uruguay in the last few years of the past century, almost ,simultaneously with their performance in sone European countries.